Image‐based embroidery modeling and rendering - Cui, Dele; Sheng, Yun; Zhang, Guixu (Computer animation and virtual worlds, 2017)
Embroidery is a traditional handicraft of sewing stitches into fabric or other materials in different patterns, and this ancient non‐photorealistic art form has not drawn enough attention thus far. In this paper, we present an image‐based method to simulate the traditional embroidery art. The method combines stroke‐based rendering techniques with the Phong lighting model to create picturesque embroidery‐like images. We first build a 3D stitch model and derive some most commonly used stitch patterns from it. Then we preprocess the input image by segmenting it into regions, from which the parameters to specify stitch patterns are obtained. Finally, we apply stitches back onto the desired regions and render them under a virtual light source. Experimental results show that our method, different from the existing schemes, is capable of performing fine embroidery simulations with the effects of lighting and shading based on an input image. Copyright © 2016 John Wiley & Sons, Ltd. This paper presents an image‐based embroidery rendering method, which combines stroke‐based rendering techniques with the Phong lighting model to generate picturesque images with embroidery style. We build a 3D stitch model and derive some most commonly used stitch patterns from it. Then we segment the input image into regions, calculate region‐wise parameters to apply single or multiple layers of stitches onto the specific regions and render them under a virtual light source to create the effects of lighting and shading.